2014
DOI: 10.3945/ajcn.113.069880
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and meta-analysis of dietary patterns and depression in community-dwelling adults

Abstract: The results suggest that high intakes of fruit, vegetables, fish, and whole grains may be associated with a reduced depression risk. However, more high-quality randomized controlled trials and cohort studies are needed to confirm this finding, specifically the temporal sequence of this association.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

28
456
1
9

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 616 publications
(494 citation statements)
references
References 44 publications
28
456
1
9
Order By: Relevance
“…This association seems to be consistent across countries, cultures and populations according to several systematic reviews and meta-analyses (26)(27)(28) . These systematic reviews included not only adults but also other populations, included retrospective or cross-sectional studies without longitudinal data and finally, occasionally included studies that really did not assess the effect of an overall food pattern, but only of food items or food groups.…”
Section: Available Longitudinal Evidence On Food Patterns and The Rissupporting
confidence: 60%
“…This association seems to be consistent across countries, cultures and populations according to several systematic reviews and meta-analyses (26)(27)(28) . These systematic reviews included not only adults but also other populations, included retrospective or cross-sectional studies without longitudinal data and finally, occasionally included studies that really did not assess the effect of an overall food pattern, but only of food items or food groups.…”
Section: Available Longitudinal Evidence On Food Patterns and The Rissupporting
confidence: 60%
“…Although medications also contribute to CVD risk factors, lifestyle factors such as poor diet (e.g. low fibre, high fat, high sugar) have been identified as independent contributors [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…As a result, mental health theories have been extended to global populations to test their applicability. In some cases, current theories have been further confirmed (e.g., Lai et al, 2014;Gupta et al, 2013), whereas in other cases they have revealed cross-cultural differences, resulting in the need to reformulate current theories (e.g., Neese, Pittman, & Hunemorder, 2013;Seiffge-Krenke et al, 2013). This has contributed to the maturation of developmental theories --such that the individual-context fit, and the bidirectional nature development are now being investigated (e.g., Lerner, 1995;Abo-Zena & Ahmed, 2014;Hafen, Spilker, Chango, Marston, & Allen, 2014).…”
Section: General Trends In Adolescent and Emerging Adulthood Researchmentioning
confidence: 99%